Estimating conductivity and interfacial polarization loss factors of oil-paper insulation for power transformers - Nimsanong, P.; Maneerot, S.; Pattanadech, N. (My University, 2020)
This paper proposes the method for categorizing the estimating conductivity and interfacial polarization loss factors of the oil-paper insulation. The simulated dielectric responses in the time domain of oil-paper insulation with various conditions were studied. Lumped equivalent circuit, so-celled extended Debye model, for modeling the oil-paper insulation obtained from simulated results, were estimated by using ohm's law for conduction current, and a curve fitting technique with exponential functions applied to the depolarization current idep(t). The complex capacitance, conductivity loss factor, and interfacial polarization loss factor of the insulation system in the frequency domain from 0.01 mHz to 1 Hz can be calculated.
Keywords: Complex capacitance; Conductivity loss factor; Debye model; Interfacial polarization loss factor